The status of p53 affects the efficacy of PLK1 inhibitor BI6727 in prostate cancer cells - Li, Wenjing; Wang, Ying; Guo, Wenzheng; Wen, Donghua (Frontiers in Cell and Developmental Biology, 2025)
As there are no effective treatments for advanced prostate cancer, exploring new therapies is crucial. BI6727(Volasertib), a PLK1 inhibitor, shows great promise as an anti-cancer drug. However, despite advancing to phase II and III trials in other cancers, BI6727 has shown limited anti-tumor activity in prostate cancer, making it crucial to investigate the underlying reasons for this discrepancy. In this study, we found that the status of p53 affects the sensitivity of prostate cancer cells to BI6727. Prostate cancer cells PC3 (long-term loss of p53 expression), DU145 (expressing mutant-type p53) and LNCaP (expressing wild-type p53) were treated with BI6727, respectively. It was found that PC3 cells were more sensitive to BI6727 when wild-type p53 was introduced into these cancer cells; while apoptosis induced by BI6727 was reduced after knockdown of p53 in LNCaP cells. In additional, in DU145 cells, the presence of points mutation in p53 exerted a dominant negative effect, attenuating BI6727-induced apoptosis. Further analysis revealed that missense mutations in the P53 gene are widespread in prostate cancer patients. Mechanistically, BI6727 reduces the degradation of Topors, thereby increasing the stability of p53 by reducing its ubiquitination. This ultimately influences the sensitivity of prostate cancer cells with different p53 statuses to BI6727.In summary, this study identifies p53 as a key factor limiting the clinical efficacy of BI6727 in prostate cancer cells.